Ethical Decision-Making in Family Firms: The Role of Employee Identification - Friederike Sophie Reck; Denise Fischer; Malte Brettel (Journal of Business Ethics, 2021)
The ethical behavior prevalent in an organization often determines business success or failure. Much research in the business context has scrutinized ethical behavior, but there are still few insights into its roots; this study furthers this line of inquiry. In line with identity work theory, we examine how employees' identification with a family business shapes internal ethical decision-making processes. Because it is individuals who engage in decision-making—be it ethical or not—our research perspective centers on the individual level. We followed an inductive, qualitative approach and conducted interviews with 19 employees in seven family businesses. We found that individuals engage in identity work when they identify as individual family firm employees and when they identify with the perceived characteristics of the family firm. These processes of identification, in turn, influence how employees cope with ethical situations. Our findings contribute to ethics and family business research, as well as to identity theory.
Keywords: 300; Family firms; Ethical decision-making; Identification process; Identity work